The Limitations of the Principle of State Responsibility in the Global Climate Change Regime - Fajrin, Fera Wulandari; Larasati, Kandi Kirana; Tombi, Johan Tri Noval Hendrian; Luthfan, Gusti Fadhil Fithrian (Uti Possidetis: Journal of International Law, 2025)
Background: The global climate crisis, driven by increasing carbon emissions, has emerged as one of the most pressing challenges in international law. Despite significant milestones such as the Kyoto Protocol and the Paris Agreement, enforcement remains weak due to their reliance on soft law mechanisms. This issue deserves scholarly attention because it raises fundamental questions about state responsibility and the effectiveness of international environmental law in addressing climate change. Methodology: This research employs a doctrinal legal approach combined with a conceptual analysis. This method was selected to critically examine the normative gaps within the texts of international agreements, specifically how "soft law" language undermines enforcement. The study relies on primary legal sources, including the text of the UNFCCC, the Kyoto Protocol, the Paris Agreement, and relevant international jurisprudence such as the ICJ Advisory Opinions. Secondary data is drawn from legal literature, journal articles, and reports on global compliance. The analysis proceeds by interpreting these instruments to determine whether existing frameworks are sufficient to uphold the principle of state responsibility.Objectives: The study aims to evaluate whether existing international legal frameworks adequately enforce the principle of state responsibility in carbon emission reduction. It seeks to identify the limitations of soft law mechanisms, assess their impact on state compliance, and explore potential avenues for strengthening accountability in the global climate regime. Findings: The research reveals that current international agreements lack binding enforcement mechanisms, enabling states to disregard commitments or withdraw without significant legal consequences. While mechanisms such as “naming and shaming” have emerged as alternatives, they primarily exert reputational pressure and remain insufficient to ensure compliance. This gap undermines the principle of state responsibility in practice. Originality/Novelty: The study highlights the urgency of transitioning from soft law to hard enforcement in climate governance. It proposes the establishment of independent enforcement authorities, binding obligations, and strengthened judicial roles, offering innovative insights into how international law can more effectively uphold state responsibility in combating climate change.